Flexible Hybrid Process for Combined Production of Heat, Power and Renewable Feedstock for Refineries : Managing seasonal energy supply and demand for heat and power in Europe. Issue 2 (1st April 2021) - Kurkela, Esa; Kurkela, Minna; Frilund, Christian; Hiltunen, Ilkka; Rollins, Benjamin; Steele, Andrew
A flexible combined heat, power and fuel production concept, FlexCHX, is being developed for managing the seasonal mismatch between solar energy supply and the demand for heat and power characteristic of northern and central Europe. The process produces an intermediate energy carrier (Fischer-Tropsch (FT) hydrocarbon product), which can be refined to transportation fuels using existing refineries. The FlexCHX process can be integrated into various combined heat and power (CHP) production systems, both industrial CHPs and communal district heating units. In the summer season, renewable fuels are produced from biomass and hydrogen; the hydrogen is produced from water via electrolysis that is driven by low-cost excess electricity from the grid. In the dark winter season, the plant is operated only with biomass in order to maximise the production of the much-needed heat, electricity and FT hydrocarbons. Most of the invested plant components are in full use throughout the year with only the electrolysis unit being operated seasonally. The catalytic reformer plays a key role in this process by converting tars and light hydrocarbon gases into synthesis gas (syngas) and by bringing the main gas constituents towards equilibrium. Developmental precious metal catalysts were used, and an optimal reformer concept was established and tested at pilot scale. Reforming results obtained at pilot gasification tests with commercial nickel catalysts and with the developed precious metal catalysts are presented.